KONSEPSI KELUARGA SAKINAH BAGI KELUARGA PERANTAU DI DESA REJOAGUNG KABUPATEN JOMBANG PERSPEKTIF MASLAHAH IMAM AL-GHAZALI - Afiat, Irfan; H.Noho, Muhammad Dzikirullah (IAIN BONE, 2025)
This research analyzes the strategies employed by wives in Rejoagung Village to maintain family harmony while navigating long-distance relationships due to their husbands working away from home. The study adopts a qualitative method with a case study approach, conducting in-depth interviews with five informants. The findings reveal that regular communication through phone calls, video calls, and text messages serves as the primary strategy to sustain emotional connection. Trust, moral support, and celebrating important moments such as birthdays also strengthen relationships, albeit virtually. These findings are examined within the framework of Al-Ghazali’s thought, particularly the concept of maslahah mursalah, which aligns with the principles of maqasid al-shariah. Communication strategies are associated with hifz al-nafs (protection of the soul), while trust and moral support relate to hifz al-nasl (protection of progeny) and hifz al-mal (protection of wealth). The study concludes that Islamic principles remain relevant in guiding Muslim families to address modern challenges such as long-distance relationships by applying shariah values that are both flexible and grounded in maqasid al-shariah.